Mosques as Catalysts for Islamic Financial Inclusion: Evidence from Branchless Banking Implementations - Trianah Sofiani; Shofian bin Ahmad; Bunga Desyana Pratami; Heris Suhendar (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2025)
Islamic financial inclusion in Indonesia remains relatively low among the unbanked and underbanked populations, who have limited access to formal banking services. This condition necessitated Bank Syariah Indonesia to introduce a branchless banking initiative, known as BSI Smart, which is integrated with mosques to expand equitable access to Islamic financial services. Therefore, this study aimed to analyze the effectiveness of implementing a branchless banking policy integrated with mosques to increase Islamic financial inclusion. The analysis adopted qualitative methods, collecting data through interviews and questionnaires. Interviews were conducted with 10 informants selected purposively. Questionnaires were further administered to 100 respondents in rural areas and 100 in urban areas who were randomly selected. Correlating with the theories of Edwards and Metter-Horn, this study showed that implementing branchless banking policy through mosques remained ineffective due to inaccurate targeting, limited facilities and infrastructure, suboptimal communication, and the community's socio-economic conditions, which tended to favor informal financial institutions. The novelty of the analysis lay in the integration of mosques as centers for Islamic financial literacy and education, directly connected to BSI Smart agents. This allowed mosques to serve as places of worship and centers of economic empowerment for the community. Additionally, the model had the potential to become a new strategy in expanding the reach of Islamic banking that was more inclusive, sustainable, and in accordance with Islamic principles.